ANALYSIS OF THE EFFECTIVENESS OF THE INTERNAL CONTROL SYSTEM OVER INVENTORY MANAGEMENT IN MEDIUM-SIZED COMPANIES - Adi, Ananta; Melati, Indah (LPPM STIE Muhammadiah Bandung, 2023)
This reserach aims to analyze and provide recommendations for improving the effectiveness of the internal control system in inventory management at PT TMT. PT TMT is a medium-sized manufacturing company specializing in elevators and escalators, where inventory serves as the main source of revenue for the company. Having a good internal control is crucial to influence PT TMT's business operations and mitigate existing risks. However, as a medium-sized company, PT TMT faces limitations in resources, infrastructure, and income, which can hinder the implementation of an effective internal control system. This research adopts a qualitative approach that refers to the COSO framework. Data collection techniques include interviews, direct observations, and analysis of PT TMT's Standard Operating Procedures (SOP) documents. Based on the research findings, it was found that PT TMT still has weaknesses in internal control related to the five components of the COSO internal control framework. This study is expected to provide accurate information regarding the internal control condition at PT TMT and offer recommendations to improve the weaknesses in the company's internal control.